2016
DOI: 10.5435/jaaos-d-15-00325
|View full text |Cite
|
Sign up to set email alerts
|

Nail Length in the Management of Intertrochanteric Fracture of the Femur

Abstract: Intramedullary devices are used increasingly to treat intertrochanteric femur fractures, especially those with unstable patterns. In spite of the considerable use of nails in the management of these fractures, opinions differ about the correct length of intramedullary nail. Long nails were developed to address the risk of diaphyseal fracture associated with earlier short nail designs and to extend the indications for use to include diaphyseal and subtrochanteric fractures. Several recent studies, however, have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…The relevance of nail length in determining PNFs is still a matter of debate [ 30 32 ]. Recently, Shannon et al in their randomized controlled trial reported a similar rate of PNFs around both short and long nails (2.4% vs. 2.7%) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of nail length in determining PNFs is still a matter of debate [ 30 32 ]. Recently, Shannon et al in their randomized controlled trial reported a similar rate of PNFs around both short and long nails (2.4% vs. 2.7%) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Daner et al in their biomechanical study did not observe any difference in stiffness between long and short nails under rotational forces, thus making the fracture risk similar [ 17 ]. These inconclusive evidences on the role of nail length in determining PNFs and the observation that a clear definition of long nail did not exist (long nails are considered those longer than 240 mm, 300 mm, and 340 mm depending on the nail and the authors [ 32 35 ]) did not lead the research group to reach a consensus on the putative role played by nail length in their PNF management.…”
Section: Resultsmentioning
confidence: 99%
“…We must admit limitations of our study including the possibility of surgeon bias towards the use of either a straight or cephallomedullary nail in certain fracture patterns, which remains hidden in our retrospective study design. Despite the fact that long nails seem to offer no clinical advantage compared to standard nails for the treatment of 31 A3 type fractures except a reduced rate of secondary femur fracture [22, 44, 45], we included only long nails. This is in accordance with the recently published algorithm for the treatment of per-/intertrochanteric fractures of the hip [19].…”
Section: Discussionmentioning
confidence: 99%
“…(1) Patients aged > 60 years; (2) Patients diagnosed with an intertrochanteric fracture after preoperative imaging examination; 9 (3) Patients without local trauma or local bone-related diseases in the past; (4) Be voluntarily recruited to the research and sign the consent form; (5) No obvious mental disorder, able to cooperate in completing the research work.…”
Section: Methodsmentioning
confidence: 99%